Association Between use of a Single-Piston CPR Device in the Resuscitation Process and the Short-Term Survival of OHCA Patients - Rirermsoonthorn, Pawaruj; Wittayachamnankul, Borwon; Tangsuwanaruk, Theerapon (Biomedical Sciences and Clinical Medicine, 2024)
Objective There is still a lack of evidence regarding the efficacy of using a single point piston without suction cup mechanical cardiopulmonary resuscitation (CPR) device in the resuscitation of out of hospital cardiac arrest (OHCA) cases in a moving ambulance setting. The aim of this study is to evaluate and compare short term survival rate return of spontaneous circulation (ROSC) of emergency medical service (EMS) delivered to OHCA patients receiving single point piston without a suction cup mechanical CPR device and manual CPR. Methods This case control study was conducted using data on OHCA patients between 1 January 2017 and 31 March 2020 using part of the Pan-Asian Resuscitation Outcomes Study (PAROS) data. Cases were classified as ROSC or no ROSC. Logistic regression analysis was used for the multivariable analysis of the primary objective. Results A total of 206 cases were included in this study, 68 ROSC cases and 138 no ROSC cases. The multivariable analysis found no significant difference in the ROSC rate of EMS delivered OHCA patients who received only manual CPR and patients who received the mechanical CPR either in the EMS (OR: 0.49, 95% confidence interval [CI]: 0.13-1.78) or the emergency department (ED) (AOR: 16.05, 95% confidence interval [CI]: 0.18-1435.78). Conclusions The use of the single point piston without suction cup CPR device in OHCA cases was not found to be inferior in terms of ROSC rate compared with manual CPR. Also, potential benefits in a prehospital setting could be provided by the device use, e.g., fewer staff required in the EMS. Use of the device should be considered in appropriate situations.